Analisis Pengembangan Sikap Disiplin Dalam Kegiatan Kepramukaan SDN Ngaliyan 01 - Hardiyanti, Shinta; Hanifatunnisa, Maulfi; Nurdina, Adinda Assyfa; Pratama, Galih Suci (Yayasan Daarul Huda Kruengmane, 2024)
This research aims to describe scout extracurricular activities at SD N Ngaliyan 01, as well as activities aimed at developing disciplinary character at the school. This research uses a qualitative approach. In this method, the researcher acts as the main instrument, and data collection is carried out through observation, interviews and documentation. The data obtained is generally qualitative in nature, with the data analysis carried out being inductive/qualitative. The focus of this research is the analysis of the implementation of scouting activities in the formation of disciplinary character at SDN Ngaliyan 01. The subjects of this research are Siaga scout students at SDN Ngaliyan 01. Data was collected through observation and interviews, then analyzed using qualitative descriptive methods. This research details scouting education as a means to improve the disciplinary character of students at SDN Ngaliyan 01. The research results show that (1) the formation of students' disciplinary character can be formed through scouting activities such as completing scouting attributes, (2) ceremonies, establishing rules or regulations , and through activities such as games which can help in the process of forming a disciplined character in students.